Short communication. Introgression of late blight (Phytophthora infestans L.) resistance from tuber-bearing Solanum wild species into cultivated potato - Gabriel, J.; Ruiz de Galarreta, J. I.; Lopez-Pardo, R.; Barandalla, L.; Alvarado, C.; Ritter, E. (Spanish Journal of Agricultural Research, 2011)
We have analyzed resistance to (Phytophthora infestans) in five progenies derived from crosses between wild tuberbearing potatoes (Solanum okadae, Solanum canacense, Solanum bukasovii, Solanum jamessii and Solanum raphanifolium) and cultivated diploid potato species (Solanum phureja, Solanum goniocalyx and a dihaploid of Solanum tuberosum). Different levels of resistance to P. infestans, from 11 to 81%, were found in leaves and tubers in the evaluated progenies. This variation indicates a variable number of major genes (R genes), minor genes and/or defeated R-genes, which have been transferred from the parental genotypes. Correlation analyses between leaf and tuber infection levels were low and not significant.